The Contribution of Women Traders in Increasing Household Economic Income in Saumlaki South Tanimbar Sub-District - Balthasar Malindar; Paulus Laratmase; Moses Feninlambir; Herlina Marlissa Urath (Yayasan Adra Karima Hubbi, 2024)
This research aims to explore the contribution of women traders in increasing household economic income in Saumlaki, South Tanimbar Sub-district. Saumlaki, as part of the Tanimbar Islands, faces complex economic challenges, especially among households. Women traders in this region have an important role in creating economic opportunities and overcoming economic difficulties in their neighborhoods. This research aims to understand the extent to which women traders contribute to increasing household economic income. This involves analyzing their role in creating employment, increasing access to economic resources, and influencing the economic development of the community. This research used a qualitative approach with in-depth interviews and observation as data collection methods. Data was analyzed through a process of coding and emerging themes to understand the impact of women traders on the household economy. The results showed that women traders have a significant role in increasing household economic income in Saumlaki. They are able to create economic opportunities, expand networks, and make a meaningful contribution to the economic development of the community. This research confirms that women traders have an important role in increasing household economic income in Saumlaki, South Tanimbar Sub-district. In this context, supporting efforts that strengthen their role in local economic development could be a relevant and strategic step in fighting poverty and improving household welfare in this region.